Entrepreneurship of Small and Medium-Sized Enterprises in Poland in the Context of the Regions and International Activity - Glinkowska, Beata (Olsztyn Economic Journal, 2019)
The main objective of this study was to identify the state of entrepreneurship of small and medium-sized enterprises in Poland in the context of individual regions and to try to identify the relationship between entrepreneurship and international activity, with particular focus on foreign direct investment. This goal was also chosen to inspire more researchers to fill the research gap in this respect. To achieve this goal, research was carried out, consisting of comparative analyses of existing official reports and documents regarding the state of entrepreneurship and internationalization, which would then show the activity of enterprises in relation to their revenues, investment expenditures and their internationalization. It should be mentioned that there are no compact, uniform studies regarding the relationship between entrepreneurship and internationalization of activities broken down into individual voivodships. It is definitely a research gap. For the purpose of this study, it was necessary to explain the fact that the author identified the international activity of enterprises with their internationalization and used this nomenclature interchangeably in this study. The author understands internationalization to be every activity of enterprise in relation to their various forms: from sporadic export and import contacts in an indirect way (i.e. through foreign intermediaries), to direct trade activities (direct export and import), cooperative contacts, strategic alliances and foreign direct investments (FDI). The study is not about showing what forms dominate in individual regions, but what the state of entrepreneurship is there, evaluated through the prism of such indicators as revenues per company from the SME sector in PLN million, investment outlays in PLN thousands and the so-called Synthetic indicator (WS). This action was performed to bring the following results: a comparison of the entrepreneurship of small and medium enterprises in Poland in relation to their regionalization and to draw attention to the relationship between the state of entrepreneurship and the state of internationalization.